Problemming of formation of landlines of territorial communities in the conditions of decentralization of the power - Priadka Т.; Drebot, O.; Komarova, N. (Land Management, Cadastre and Land Monitoring, 2018)
One of the main tasks of the decentralization reform is to strengthen the role of territorial communities with the provision of their right to dispose of land, both within and outside settlements. The article analyzes the tendencies of decentralization of power in the Kyiv region. Keywords: Decentralization of power, management of land resources, united territorial community, problems of modern land use.